Pengembangan Modul Ajar Berstrategi Mind Mapping untuk Meningatkan Keterampilan Berpikir Kreatif pada Materi Ikatan Kimia - Cici Aprilia; Mitarlis (PendIPA Journal of Science Education, 2023)
This study aimed to describe the feasibility of teaching modules with mind mapping strategies to improve creative thinking skills in chemical bonding material. The research method used was the 4-D model (define, design, develop and disseminate) which is limited to the development stage. The trial was conducted on 34 students of class XII IPA 4 at one of state senior high school in Surabaya. The teaching module was said to be feasible in terms of validity, practicality and effectiveness. The results showed the feasibility of teaching modules in terms of content validity getting mode 5 on very good category and construct validity getting mode 4 on good category so that overall the teaching module gets mode ≥4 and is declared valid. The practicality of teaching modules in terms of learning implementation gets a percentage of 93.63%, student activities get a percentage of 97.35% and student responses with a percentage of 92.12% with very practical criteria. The effectiveness of the teaching modules is seen from the improvement of students' creative thinking skills through pretest and posttest mind mapping as well as questions on the description of creative thinking skills on chemical bonding material with an N-Gain value obtained respectively of 0.73 and 0.72 in the high category. Based on the results of validity, practicality and effectiveness can be concluded that teaching modules with mind mapping strategies are appropriate to be used in learning to improve creative thinking skills in chemical bonding material.